Sestrin2 as a Potential Target for Regulating Metabolic-Related Diseases - Gong, Linan; Wang, Zanzan; Wang, Zhenggui; Zhang, Zhiguo (Frontiers in Endocrinology, 2021)
Sestrin2 is a highly conserved protein that can be induced under a variety of stress conditions, including DNA damage, oxidative stress, endoplasmic reticulum (ER) stress, and metabolic stress. Numerous studies have shown that the AMP-activated protein kinase (AMPK)/mammalian target of rapamycin (mTOR) signaling pathway has a crucial role in the regulation of metabolism. Sestrin2 regulates metabolism via a number of pathways, including activation of AMPK, inhibition of the mTOR complex 1 (mTORC1), activation of mTOR complex 2 (mTORC2), inhibition of ER stress, and promotion of autophagy. Therefore, modulation of Sestrin2 activity may provide a potential therapeutic target for the prevention of metabolic diseases such as insulin resistance, diabetes, obesity, non-alcoholic fatty liver disease, and myocardial ischemia/reperfusion injury. In this review, we examined the regulatory relationship between Sestrin2 and the AMPK/mTOR signaling pathway and the effects of Sestrin2 on energy metabolism.